Delimitation and description of cryptic species: lessons from the systematics of Aurelia (Cnidaria, Scyphozoa) - Lawley, Jonathan Wanderley (2018)
The delimitation and description of species, the fundamental units of biology, have puzzled scientists for centuries. Their identities were traditionally recognized based on distribution, ecology and most of all, morphology. Molecular data have recently come into play, and nowadays form an important component of most systematic studies. Many methods have been quickly devised and applied to integrate these data in the species delimitation and description process, and they have been accompanied not only by exciting possibilities and discoveries, but also by new questions and challenges. Some epistemological issues appear from recent proposals that suggest congruency across methods, or even operational criteria, as evidence for delimitation. Also, the discovery of morphologically indistinguishable genetic lineages, described as \'cryptic\', has hindered recognition and formal assessments of biological diversity. In Chapter 1, I address epistemological reasoning that encircles discovery operations, methods and congruency for evidence-based species delimitation. We discuss that congruence across methods or operational criteria, if based on the same data, are exclusive discovery operations and therefore have no epistemic value as evidence. Issues regarding some methods are also highlighted, including coalescent theory, DNA barcoding, and even phylogenetic systematics. In Chapter 2, I move into the application of species delimitation and description in Aurelia (Cnidaria, Scyphozoa). A morphological reassessment of medusae specimens from across the globe revealed no geographic structure on dissimilarities, with considerable morphological variation within collection lots and even within hypothesized species. This morphological plasticity had already been reported for medusae in some Aurelia, as well as in the polyp and ephyra stages. Considering this crypsis, multi-marker molecular analyses and distribution records were used to delimit and describe species. I also address the unreliability of DNA barcoding for species delimitation and its limitations even for identification. The reported diagnostic molecular characters not only fill the requirements for descriptions, but also hint on the possibility of its practical uses for identification, rather than barcoding. This study should encourages future research not only on delimitation and description of cryptic diversity, which should include careful scrutiny of methods and data used, but also on morphological plasticity and the patterns and processes involved in generating crypsis